Marketing Strategy of Financing Products in an Effort to Increase the Number of Customers at Baitul Mal Wat Tamwil (BMT) Rizwa Manbaul Ulum Rejotangan Tulungagung - Reni Waningsih; Rizma Denytasari; Agus Eko Sujianto (Jurnal Syntax Transformation, 2024)
This study aims to evaluate the marketing strategy of financing products implemented by Baitul Mal Wat Tamwil (BMT) Rizwa Manbaul Ulum Rejotangan Tulungagung and identify inhibiting and supporting factors in the implementation of financing product marketing strategies in BMT. This study used qualitative research methods, which include observation and interviews. The results showed that BMT Rizwa Manbaul Ulum Rejotangan Tulungagung used a marketing strategy through distributing brochures to the public. Thus, this strategy has not attracted significant customer interest. In addition, there are still certain areas in the red zone criteria, in the sense that the red zone criteria here are the existence of certain community areas that are included in the community area that have negative characters or thoughts about financing products at BMT Rizwa Manba'ul 'Ulum, for example, there are some people who think that financing products at BMT Rizwa Manba'ul 'Ulum have very difficult and burdensome requirements. Therefore, this study suggests improving marketing strategies implemented by BMT Rizwa Manbaul Ulum Rejotangan Tulungagung, such as taking a family approach, promoting through social media, distributing brochures to a wider area, conducting socialization to the surrounding community, and installing banners in front of the BMT office. In addition, this study also confirms the importance of collaboration and cooperation between Islamic financial institutions and other parties in increasing the number of customers and the development of BMT.